Calculate the multifactorial 7!!
We have 2 exclamation symbols (!)
Start at 7
Iterate backwards in steps of 2
Stop when we hit 1 or below
For term 1, we start with 7
Subtract -1 x 2 = -2 to get n(n - -2)
(n - -2) → 7 - -2 = 5
Our factorial term is:
7(5)
Subtract -1 x 2 = -2 to get n(n - -2)(n - -2)
(n - -2) → 7 - -2 = 3
Our factorial term is:
7(5)(3)
Subtract -1 x 2 = -2 to get n(n - -2)(n - -2)(n - -2)
(n - -2) → 7 - -2 = 1
Our factorial term is:
7(5)(3)(1)
7!! = n(n - -2)(n - -2)(n - -2)...
7!! = 7(5)(3)(1)